HUBUNGAN PENDAPATAN KELUARGA DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH PUSKESMAS SEGINIM KABUPATEN BENGKULU SELATAN - ruri maiseptya sari (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2020)
Stunting or short is a failure to grow in infants (0-11 months) and toddlers (12-59 months), due to lack of nutrition, especially in the first 1000 days of life so that children are too short for their age. The purpose of this study was to study the relationship of family income with the incidence of stunting in infants in Seginim Health Center, South Bengkulu Regency. The method of this research is descriptive correlational, using cross-sectional design. Accidental sampling technique in which the samples in the study were found during the study were 32 respondents. The data obtained are then processed and analyzed using univariate analysis and bivariate analysis using chi-square analysis and contingency coefficient. The results of this study are: out of 32 toddlers there are 12 toddlers who experienced stunting and 20 toddlers (62.5%) did not experience stunting and from 32 respondents there were 10 respondents who had low incomes, 17 toddlers (53.1%) had moderate incomes and 5 respondents have high income. There is a relationship between family income and the incidence of stunting in infants in the Seginim Community Health Center in the South Bengkulu Regency. Statistical test results: Pearson chi-square value χ2 = 11.219 with p-value = 0.004 <0.05 means significant, then Ho is rejected and Ha is accepted. So there is a relationship between family income and the incidence of stunting in children under five in the Seginim Community Health Center in South Bengkulu Regency. It is expected that the South Bengkulu Seginim Puskesmas institute is expected to increase parents' knowledge about the benefits and importance of nutrition for toddlers.